The processes of transport and public health policy change: 20mph speed limits in Edinburgh and Belfast. Issue 3 (September 2022) - Milton, K.; Turner, K.; Baker, G.; Cleland, C.L.; Foster, C.; Hunter, R.F.; Jepson, R.; Kee, F.; Kelly, P.; Kelly, M.P.
Highlights: In 2016, large scale 20mph speed limit interventions were implemented in Edinburgh and Belfast. Using a qualitative case study method, this paper describes how 20mph speed limit interventions became a reality in the two cities. Both interventions are examples of radical incrementalism to achieve transport and public health policy change. The gradualist approach proved successful in gaining support for the interventions and minimising political and public opposition. These successes in policy change provide useful learning for other jurisdictions planning or thinking about similar interventions. Abstract: Background: In 2016, large scale 20mph speed limits were implemented in the cities of Edinburgh (Scotland) and Belfast (Northern Ireland). The fact that both cities succeeded in implementing 20mph speed limit interventions is important. They illustrate the processes of transport and public health policy change. This paper describes how 20mph speed limit interventions became a reality in the two cities. Methods: We adopted a qualitative case study method. Data were collected from available documents and interviews with stakeholders involved in the pre-implementation processes. Documents and interviews were analysed inductively using thematic analysis, and separately for each city. Results: Five main themes were generated through the analysis: the national policy context of the two cities; political leadership; support for 20mph; opposition; and the key actions involved prior to implementation. Conclusions: In both cities the process took place over at least a ten year period and was piecemeal. However, the gradualist approach proved successful in gaining support for the schemes and minimising political and public backlash. These examples of policy success in Edinburgh and Belfast provide useful learning for other jurisdictions planning or thinking about similar transport and public health policy changes.